Bony maturation study in young patients from odontological clinic of the UNMSM . - Orellana M., Tomás Oriel (2006)
The purpose of this study consisted in determining the stages of bony maturation according to the classification of Helm and Björk, in 80 children patients who went for orthodontic treatment to the clinic of the Faculty of Odontology of UNMSM. Of the total of children, 38 were females and 42 were males. The ages oscillated between 7 and 13 years of age. The results indicated that in the children, the stage MP3 cap that correspond to the growth tip found at the age of 10.29 years whereas in males the same phase occurred at the age of 12.12 years. These results demostrate that the Peruvian population matures early in relation to other population like the European.